2021
DOI: 10.1111/ijcp.14882
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in electrolyte imbalances caused by SARS‐CoV‐2: A cross‐sectional study

Abstract: Background Since SARS‐CoV‐2 spread, evidence regarding sex differences in progression and prognosis of COVID‐19 have emerged. Besides this, studies on patients' clinical characteristics have described electrolyte imbalances as one of the recurrent features of COVID‐19. Methods We performed a cross‐sectional study on all patients admitted to the emergency department (ED) from 1 March to 31 May 2020 who had undergone a blood gas analysis and a nasopharyngeal swab test for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Hypocalcemia cases with Covid-19 in male patients were between 28% to 34% than female patients, namely 16% to 32%. This difference was associated with the vitamin D or calcium supplements consumption in women who are more often for osteoporosis prevention 11 .…”
Section: Discussionmentioning
confidence: 98%
“…Hypocalcemia cases with Covid-19 in male patients were between 28% to 34% than female patients, namely 16% to 32%. This difference was associated with the vitamin D or calcium supplements consumption in women who are more often for osteoporosis prevention 11 .…”
Section: Discussionmentioning
confidence: 98%
“…8 In addition, SARS-CoV-2 may affect sodium and potassium transport via Na+/K+ ATPase in renal tubular epithelium through ACE2-related renin-angiotensin system activation. 9 Post-mortem studies in patients who died due to COVID-19 revealed the presence of significant acute tubular injury in light microscopy, while the presence of viral particles in both tubular epithelium and podocytes was shown in electron microscopy, which has been attributed to direct infection of the kidneys by COVID-19. 10,11 In a study conducted in France, it was suggested that the findings of proteinuria, hypophosphatemia, hypouricemia, and glycosuria are common in patients who developed proximal tubule damage due to COVID-19 and that these findings can be used as markers of proximal tubule damage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted sex differences in electrolyte imbalances caused by SARS-CoV-2 at the acute phase 7 . Moreover, such electrolyte patterns have been associated with COVID-19 disease in hospitalised patients 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as long COVID symptoms are more likely to occur in females 4 , we expected that patients’ sex might interact with the disease severity in the odds of persistent cognitive difficulties. Lastly, as electrolyte imbalances are one of the recurrent features of COVID-19, and it differs between males and females 7 , we hypothesised that the odds of cognitive failures could be associated with the electrolyte profile during the hospitalisation, particularly in female patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation